Direction of Arrival Estimation in Linear Arrays by a Novel Hybrid Algorithm - Muhammed Fahri Unlersen; Ercan Yaldiz (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, a new hybrid algorithm for uniform linear antenna (ULA) array was composed by using First Order Forward Prediction (FOFP) and the Minimum Variance Distortionless Response (MVDR) algorithms together. FOFP and MVDR algorithms were discussed as incident signal direction prediction algorithms. The powerful and weak points of these two algorithms were explained. Some scripts were written by using MATLAB. 5 antennas which were spaced with half wavelength, forms an ULA array. Its output data was used as input data of the three algorithms mentioned above. The results obtained from the hybrid algorithm and the individual results of MVDR and FOFP algorithms were compared under the same conditions. An improvement in the proposed hybrid algorithm is observed.